Posterior spinal fusion using a unilateral C1 posterior arch screw and a C2 laminar screw for atlantoaxial fracture dislocation. (May 2019) - Ono, Yuichi; Miyakoshi, Naohisa; Hongo, Michio; Kasukawa, Yuji; Ishikawa, Yoshinori; Kudo, Daisuke; Kimura, Ryota; Iida, Jumpei; Shimada, Yoichi
Introduction: C1 lateral mass screws and C2 pedicle screws are usually chosen to fix atlantoaxial (C1–C2) instability. However, there are a few situations in which these screws are difficult to use, such as in a case with a fracture line at the screw insertion point and bleeding from the fracture site. A new technique using a unilateral C1 posterior arch screw and a C2 laminar screw combined with a contralateral C1 lateral mass screws–C2 pedicle screws procedure for upper cervical fixation is reported. Case Report: A 24-year-old woman had an irreducible C1–C2 anterior dislocation with a type III odontoid fracture on the right side due to a traffic accident. The patient underwent open reduction and posterior C1–C2 fixation. On the left side, a C1 lateral mass screws and a C2 pedicle screws were placed. Because there was bleeding from the fracture site and a high-riding vertebral artery was seen on the right side, a C1 posterior arch screw and a C2 laminar screw were chosen. Eight months after the surgery, computed tomography scans showed healing of the odontoid fracture with anatomically correct alignment. Conclusions: Although there have been few comparable studies, fixation with unilateral C1 posterior arch screw–C2 laminar screw could be a beneficial choice for surgeries involving the upper cervical region in patients with fracture dislocation or arterial abnormalities.